Dose-response to inhaled glycopyrrolate delivered with a novel Co-Suspension™ Delivery Technology metered dose inhaler (MDI) in patients with moderate-to-severe COPD. Issue 1 (December 2016) - Fabbri, Leonardo; Kerwin, Edward; Spangenthal, Selwyn; Ferguson, Gary; Rodriguez-Roisin, Roberto; Pearle, James; Sethi, Sanjay; Orevillo, Chad; Darken, Patrick; St. Rose, Earl; Fischer, Tracy; Golden, Michael; et al.
Abstract Background This study forms part of the first complete characterization of the dose–response curve for glycopyrrolate (GP) delivered using Co-Suspension™ Delivery Technology via a metered dose inhaler (MDI). We examined the lower GP MDI dose range to determine an optimal dose for patients with moderate-to-severe chronic obstructive pulmonary disease (COPD). Methods This randomized, double-blind, chronic-dosing, balanced incomplete-block, placebo-controlled, crossover study compared six doses of GP MDI (18, 9, 4.6, 2.4, 1.2, and 0.6 μg, twice daily [BID]) with placebo MDI BID and open-label tiotropium dry powder inhaler (18 μg, once daily [QD]) in patients with moderate-to-severe COPD. Patients were randomized into 1 of 120 treatment sequences. Each sequence included 4 of 8 treatments administered for 14-day periods separated by 7- to 21-day washout periods. The primary efficacy endpoint was change from baseline in forced expiratory volume in 1 s area under the curve from 0 to 12 h (FEV1 AUC0–12 ) on Day 14. Secondary efficacy endpoints included peak change from baseline (post-dose) in FEV1 and inspiratory capacity (IC) on Days 1, 7, and 14; change from baseline in morning pre-dose trough FEV1 on Days 7 and 14; change from baseline in 12-h post-dose trough FEV1 on Day 14; time to onset of action (≥10 % improvement in mean FEV1 ) and the proportion of patients achieving ≥12 % improvement in FEV1 on Day 1; and pre-dose trough IC on Days 7 and 14. Safety and tolerability were also assessed. Results GP MDI 18, 9, 4.6, and 2.4 μg demonstrated statistically significant and clinically relevant increases in FEV1 AUC0–12 compared with placebo MDI following 14 days of treatment (modified intent-to-treat population = 120). GP MDI 18 μg was non-inferior to open-label tiotropium for peak change in FEV1 on Day 1 and morning pre-dose trough FEV1 on Day 14. All doses of GP MDI were well tolerated with no unexpected safety findings. Conclusions These efficacy and safety results support GP MDI 18 μg BID as the most appropriate dose for evaluation in Phase III trials in patients with moderate-to-severe COPD. Trial registration ClinicalTrials.govNCT01566773 . Registered 27 March 2012.